Naslavljanje med žensko in moškim v slovenskem romanu - Modrijan, Nina (Jezik in slovstvo, 2005)
Forms of address are defined as part of the grammar of social status, foregrounding the study of socia relations based on either power or solidarity, which is expressed through certain linguistic means: forms of address. The main objective was to study forms od address between nine literary characters (three women and six men), and the influence of linguisticand other social factors available, as well as the use of these linguistic means. Three Slovene novels were analyses: Lepa Vida (Beautiful Vida( by Josip Jurčič, V krvi (In blood) by Fran Govekar, and Gospa Judit (Madam Judit) by Ivan Cankar. The combining of sociolinguistics and literary studies, or addressing and analysing dialogues, results in the social and stylistic portrayal of female and male characters in Slovene novels at the turn of the 19th an d20th centuries.
Keywords: Cankar; Cankar, Ivan; Govekar, Fran; Ivan Cankar; Jurčič, Josip; literarne študije; man; moški; naslavljanje; novel; roman; Slovene literature; slovenska književnost; sociolingvisitka; stilisitka; woman; ženske